2003
DOI: 10.1002/gcc.10283
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant expression of the LHX4 LIM‐homeobox gene caused by t(1;14)(q25;q32) in chronic myelogenous leukemia in biphenotypic blast crisis

Abstract: Chromosomal aberrations observed in addition to the Philadelphia chromosome in chronic myelogenous leukemia (CML) are likely to be involved in disease progression to the blast crisis. We describe here a t(1;14)(q25;q32) as an additional chromosomal aberration in a patient with CML in biphenotypic blast crisis. By use of long-distance inverse polymerase chain reaction (PCR), we cloned the chromosomal breakpoint and revealed that the immunoglobulin heavy chain gene is fused near its Emu enhancer region to the 5'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…In cellular transformation assays, using Rat1 and NIH3T3 cell lines, the oncogenic activities of the LHX4 gene could not be defined (Kawamata et al, 2002), but aberrant expression of this gene was observed in the case of chronic myeloid leukemia in blast crisis and in the case of pre-B acute lymphoblastic leukemia. Both cases carried a t(1;14)(q25;q32) chromosome translocation, which The SSX C terminus interacts with LHX4 DRH de Bruijn et al resulted in juxtaposition of the respective LHX4 and IGH genes (Kawamata et al, 2002;Yamaguchi et al, 2003). The LHX4 gene was also found to be overexpressed in the pre-B acute lymphoblastic leukemia cell line MD930 (Yamaguchi et al, 2003).…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…In cellular transformation assays, using Rat1 and NIH3T3 cell lines, the oncogenic activities of the LHX4 gene could not be defined (Kawamata et al, 2002), but aberrant expression of this gene was observed in the case of chronic myeloid leukemia in blast crisis and in the case of pre-B acute lymphoblastic leukemia. Both cases carried a t(1;14)(q25;q32) chromosome translocation, which The SSX C terminus interacts with LHX4 DRH de Bruijn et al resulted in juxtaposition of the respective LHX4 and IGH genes (Kawamata et al, 2002;Yamaguchi et al, 2003). The LHX4 gene was also found to be overexpressed in the pre-B acute lymphoblastic leukemia cell line MD930 (Yamaguchi et al, 2003).…”
Section: Discussionmentioning
confidence: 98%
“…The LHX4 gene was also found to be overexpressed in the pre-B acute lymphoblastic leukemia cell line MD930 (Yamaguchi et al, 2003). During normal development, the LHX4 gene is predominantly expressed in the central nervous system (Liu et al, 2002), and it was proposed that its overexpression may be associated with cellular proliferation and/or anti-apoptosis (Kawamata et al, 2002;Yamaguchi et al, 2003). Indeed, mouse knockout studies revealed that LHX4 deficiency leads to an increased apoptotic rate in Rathke's pouch, resulting in an impaired pituitary development reminiscent of human congenital pituitary hormone deficiency (CPHD; Sheng et al, 1997;Machinis et al, 2001;Raetzman et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations